Tantangan Dan Prospek Netralitas Birokrasi Dalam Pemilu 2024 : (Studi Kasus Di Kabupaten Bima) - Sadrul Imam; Mukhlis Ishaka; Syamsuddin Syamsuddin (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
This research aims to explain the challenges and prospects of bureaucratic neutrality in the 2024 Election in Bima Regency. This study utilizes a qualitative descriptive method and literature review. The research location is in Bima Regency, which is strategically situated to examine case studies and the issues at hand. Data collection techniques consist of literature review, observation, interviews, and documentation. After collecting complete data from the field, the next step is the data analysis phase. In this research, the data analysis technique employs the interactive model, consisting of three main elements: data reduction, data presentation, and conclusion/verification. The research findings indicate that maintaining bureaucratic neutrality in the 2024 Election in Bima Regency requires rigorous oversight, cooperation among relevant institutions, and the enhancement of bureaucratic human resources' quality. Civil servants (ASN) also need to understand the importance of maintaining their neutrality in the 2024 Election to prevent identity politicization, political funding, and the spread of hoaxes. Regulations and guidelines also play a crucial role in preserving bureaucratic neutrality during the elections.